The PENDIDIKAN AGAMA ISLAM DAN KESADARAN EKOLOGIS: TRANSFORMASI PENDIDIKAN GREEN PESANTREN DALAM MEWUJUDKAN ZERO-WASTE BOARDING SCHOOL: PENDIDIKAN AGAMA ISLAM DAN KESADARAN EKOLOGIS: TRANSFORMASI PENDIDIKAN GREEN PESANTREN DALAM MEWUJUDKAN ZERO-WASTE BOARDING SCHOOL - rahman, jazilur; Muftiddini Kumala, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to describe and provide an in-depth analysis of Islamic Religious Education and Ecological Awareness: the Transformation of Green Pesantren Education in Realizing a Zero-Waste Boarding School at Nurul Jadid Islamic Boarding School, Paiton, Probolinggo. This study employed a qualitative research approach using a case study design. The research was conducted at Nurul Jadid Islamic Boarding School, Paiton, Probolinggo, from September to November 2025. Data were collected through interviews, observations, and documentation. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the transformation toward a green pesantren is manifested through the integration of Islamic and ecological values within the pesantren education curriculum, a paradigm shift in Islamic Religious Education learning toward a green pesantren orientation, innovation in environmentally based (ecological) Islamic Religious Education learning, the implementation of a clean pesantren through sanitation and environmental hygiene management, the establishment of an Integrated Waste Management Facility, and the development of green pesantren initiatives through tree planting and garden creation.